Developing gender-transformative innovation packages for sustainable intensification: The case of maize leaf stripping in northern Ghana - Fischer, Gundula; Jimah, Kipo; Mumuni, E.; Abdul Rahman, Nurudeen; Glover, F.; Weseh, A. (Informa UK Limited, 2024)
Sustainable agricultural intensification (SI) seeks to address multiple development objectives at the same time, among them social aspects of sustainability. However, interest in gender norms as potential catalyzers or obstacles for achieving these objectives has remained low. In this article, we use a SI assessment framework as an analytical lens for the identification of social aspects—in particular inequitable norms—that could be targeted through gender-transformative innovation packages. We evaluate social science data from a maize-livestock intervention in Ghana. In a mixed methods study, data were collected from 60 farmers involved in experimentation. The analysis unearthed a number of overlapping norms that shape men’s and women’s actions and interact with the SI package to produce tangible inequalities. To promote gender equity, these norms need to be targeted. But it will not suffice to simply add gender-transformative components to technical packages, if the technical components are not redesigned to fit the same equity goal. We showcase this using the results. An important conclusion is that assessments of both social and technical components of interventions must be more consciously designed in transdisciplinary processes—with equitable arrangements in mind.